Project on Human Development in Chicago Neighborhoods (PHDCN): Household Composition, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Household Composition listing, administered to either the primary caregivers of subjects belonging to Cohorts 0 to 15, or to the subjects belonging to Cohort 18. It obtained basic information on the composition of the subject's household and included each household member's age, gender, and relationship to the subject. In Wave 1, this information was incorporated into the Family Structure and Health History (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): FAMILY STRUCTURE AND HEALTH HISTORY, WAVE 1, 1994-1997 [ICPSR 13592]).